What affects second language vocabulary learning? Evidence from multivariate analysis - Sun, Danning; Chen, Zihan; Zhu, Shanhua (Frontiers in Education, 2023)
Introduction Vocabulary acquisition is crucial in second language (L2) learning and can be affected by multi-variables. The fact that all these variables have typically been investigated separately (or, at best, in pairs) potentially obscures important interactions between them. This study comprehensively examines the intricate factors affecting vocabulary knowledge among Chinese learners studying English as a foreign language (EFL). Methods We conducted an investigation involving 200 Chinese EFL learners to identify the relationships between L2 proficiency, vocabulary learning strategies, age of acquisition (AoA), classroom exposure, and their relationships and predictive power on L2 vocabulary breadth and vocabulary depth. Results L2 proficiency emerged as the most robust predictor of vocabulary knowledge, closely trailed by vocabulary learning strategies, AoA, and classroom exposure. Notably, the use of metacognitive learning strategies such as self-regulated and self-aware learning, was found to be significant. Earlier L2 exposure resulted in a more sufficient vocabulary knowledge. However, the conventional belief that longer classroom sessions lead to enhanced vocabulary knowledge was challenged. Discussion Our findings suggest the interconnectedness between L2 proficiency and L2 vocabulary knowledge. The investigation highlights the need for increased cognitive involvement and self-discipline in L2 vocabulary learning. This study also emphasizes the necessity to maximize the efficacy of classroom sessions, together with the benefits for an earlier age of L2 acquisition. Guidance for L2 researchers and instructors in second language vocabulary acquisition is offered.